The Impact of the Formation of the Farmer Cadet Group on the Welfare of Farmer Group Members in Pohan Julu Village, Siborong-Borong District, North Tapanuli Regency - Simson Simanjuntak; Bengkel Ginting (PT FORMOSA CENDEKIA GLOBAL, 2024)
The farmers' group is a crucial point in implementing and translating the concept of farmers' rights into policies, strategies, and viable programs as a cohesive unit and as a platform for the transformation and development of the agricultural sector. A farmers' group is always formed with the aim of meeting various farmers' needs and serving as a means to address farmers' issues. The agricultural sector remains the primary source of income for the majority of the farming community, so agricultural development through farmers' groups continues to be carried out to achieve the welfare of farmers. The purpose of this research is to examine the impact of the formation of the youth farmers' group on the welfare of its members in the village of Pohan Julu, Siborongborong sub-district, North Tapanuli district. This research is a descriptive qualitative study. Data collection was carried out through observation, interviews, and documentation. The results of this research indicate that the formation of the youth farmers' group has had an impact on the improvement of the welfare of its members. This is based on eight welfare indicators issued by the Central Statistics Agency (BPS), namely education, housing, income, consumption and social patterns, which have seen improvements, but the health and population status of group members have not changed.